Learning from Anangu Histories: Population Centralisation and Decentralisation Influences and the Provision of Schooling in Tri-state Remote Communities. Issue 2 (31st December 2015) - Osborne, Sam
Abstract : Remote Australian Aboriginal and Torres Strait Islander schools and communities are diverse and complex sites shaped by contrasting geographies, languages, histories and cultures, including historical and ongoing relationships with colonialism, and connected yet contextually unique epistemologies, ontologies and cosmologies. This paper explores the history of An angu (Pitjantjatjara, Yankunytjatjara, Ngaanyatjarra and Ngaatjatjarra) populations, including the establishment of incorporated communities and schools across the tri-state remote region of central Australia. This study will show that An angu have a relatively recent contact history with Europeans and An angu experiences of engagement with colonisation and schooling are diverse and complex. By describing historical patterns of population centralisation and decentralisation, I argue that schooling and broader education policies need to be contextually responsive to An angu histories, values, ontologies and epistemologies in order to produce an education approach that resists colonialist social models and assumptions and instead, works more effectively towards a broader aim of social justice. Through assisting educators and policy makers to acquire a clearer understanding of An angu histories, capacities and struggle, I hope to inform a more nuanced, contextually responsive and socially-just consideration of the provision of Western education in the tri-state region.